Annual Report 2000-01 - Planning Commission (Planning Commission, 2000)
Revision of the plan targets and recasting of the economic parameters in conformity with the new series of NAS. while maintaining the inter sectoral consistency, have been carried out in the Midterm Term Appraisal of the Ninth Plan which was considered by the full Planning Commission in its meeting held on 30th September. 2000. The reformulation of the Plan targets and macro-economic parameters retains the target growth rate of 6.5 per cent and agricultural growth rate of 3.9 per cent per annum for the full five year period as mandated by the NDC. The revised sectoral growth rates are 5.1 per cent for mining and quarrying. 7.1 per cent for manufacturing, 8.4 per cent for electricity, gas and water supply. 6.8 per cent for construction and 11.9 per cent for communication, among others. The revised behavioural parameters are an investment rate of 25.7 per cent and a domestic savings rate of 24.27 per cent of GDP al market prices pulling down the Current Account Deficit to 1.43%.
Government of India Planning Commission
Government of India Planning Commission